PENGARUH PEMBERIAN EKSTRAK BUAH PARE (MOMORDICA CHARANTIA) TERHADAP GAMBARAN HISTOPATOLOGI ORGAN TRAKEA PADA TIKUS WISTAR YANG DIINDUKSI OBAT NYAMUK BAKAR - Utami, Tania Mulia; Lubis, Humairah Medina Liza; Delyuzar, Delyuzar; Sutysna, Hendra (JURNAL IBNU SINA BIOMEDIKA, 2018)
Background: indonesia is a tropical country and has two seasons, there are summer and rainy season. This condition willÂ  increase the population of mosquito especially in transition period. The producer of insect-repellent use this opportunity to make mospuito coil. In fact, mosquito coil is dangerous for the healthy of trachea. There are many herbs has been investigated, including pare, because it contains antioxidant. Objective: This experiment is about the effect of pareâs extract (Momordica charantia) inÂ  histopathology of trachea in wistar mouse which is induced by mosquito coil. Method : laboratoric experiment with posttest only with control group design. Mouses divide into 4 groups and will be treat for 30 days. After that, the extract will be given in250mg/bw and500mg/bw. This experiment will examine the histopathology of trachea with HE andÂ  light microscope. The data will be analyzed with Kruskal-wallis post Hoc Mann-Whitney. Result: there are significant diffrentiationÂ  in degeneration, metaplasia, necrosis, and mucose thickening score in experiment and control group. Giving 250mg/bw and 500mg/bw of pareâs extract show improvement in trachea tissue. Conclusion: giving mosquito coil can induce the damage of trachea tissue with degeneration, metaplasia, necrosis and mucose thickening process. Giving pareâs extract as antioxidant show the improvement of trachea histopathologyKeywords: pareâs extract, mosquito coil, trachea histopathology, flavonoid.